Italy : Staff Report for the 2001 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2001)
Italy has made impressive strides in achieving deep-rooted macroeconomic stability. But growth has disappointed over the past decade. The government has laid out a bold agenda to reinvigorate growth. Specifics of an expenditure and tax reform agenda should be laid out early. A key to achieving more dynamic growth is to tackle the root causes of Italy's large regional imbalances and labor market weakness. Although the liberalization of product markets has been advancing, major scope remains to promote competition and efficiency.